Men who have sex with men in southern Vietnam report high levels of substance use and sexual risk behaviours but underutilise HIV testing services: a cross-sectional study. (2nd September 2014) - Pham, Quang Duy; Nguyen, Thuong Vu; Nguyen, Phuc Duy; Le, San Hoang; Tran, Anh Tho; Nguyen, Long Thanh; Wilson, David Peter; Zhang, Lei
Abstract : Objectives: This study aims to investigate the levels and correlates of unprotected anal intercourse (UAI), drug and alcohol use, and HIV testing among Vietnamese men who have sex with men (MSM). Methods: A total of 381 MSM were recruited in a community-based cross-sectional survey in two towns (Long Xuyen and Chau Doc) in An Giang province in 2009 by using a two-stage cluster sampling. Face-to-face interviews were conducted to elicit respondents' characteristics. Regression analysis was used to determine the correlates of key behavioural outcomes. Results: In the month before being interviewed, 19.9% respondents had used drugs (13.6% injected), 25.2% had consumed alcohol daily and 33.9% had a UAI with ≥2 male partners. Only 19.2% were tested for HIV in the 12 months before being interviewed. Injecting drug use was significantly associated with having sexual partners who also inject, whereas daily alcohol consumption was associated with an ever-married/cohabiting with women, being transgender and having had at least three male partners in the previous 3 months. Transactional sex, weekly alcohol use, early sexual debut and perception of being at higher risk of HIV infection were correlates of UAI in multiple partnerships. MSM who self-identified as not being gay and those who perceived themselves to be at low risk of HIV infection were less likely to test for HIV. Conclusions: Due to the scarcity of effective MSM-targeted prevention programmes, it is likely that substance use, risky sexual behaviours and low testing uptake may substantially contribute to the spread of HIV among Vietnamese MSM sampled. Harm reduction programmes targeting MSM, and in particular injecting MSM, should be rolled-out in this province.